2007
DOI: 10.1080/10420150601135555
|View full text |Cite
|
Sign up to set email alerts
|

Range and etching behaviour of swift heavy ions in polymers

Abstract: Aliphatic (CR-39) and aromatic (Lexan polycarbonate) polymers have been irradiated with a variety of heavy ions such as 58 Ni, 93 Nb, 132 Xe, 139 La, 197 Au, 208 Pb, 209 Bi, and 238 U having energy ranges of 5.60-8.00 MeV/n in order to study the range and etching kinetics of heavy ion tracks. The ion fluence (range ∼10 4 -10 5 ions/cm 2 ) was kept low to avoid the overlapping of etched tracks. The measured values of maximum etched track length were corrected due to bulk etching and over etching to obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In addition to this post irradiation factor is also a probable factor for the formation of such bonds. Similar results have been reported in case of heavy ion irradiated polymers [9][10]. Another significant observation is the growth of band near 3310 cm -1 on irradiation, which is characteristic sp-hybridized C-H stretching mode of alkyne end group.…”
Section: Ftir Analysissupporting
confidence: 76%
“…In addition to this post irradiation factor is also a probable factor for the formation of such bonds. Similar results have been reported in case of heavy ion irradiated polymers [9][10]. Another significant observation is the growth of band near 3310 cm -1 on irradiation, which is characteristic sp-hybridized C-H stretching mode of alkyne end group.…”
Section: Ftir Analysissupporting
confidence: 76%
“…This contradicts the intuitive view that the track etch rate should increase with increasing energy which has persisted since track etching was evaluated using mainly optical techniques in crystalline materials. Singh et al [42], report on the range of swift heavy ions in polycarbonate which they have observed by subsequently etching the ion tracks and measuring their length using optical microscopy. The track etch rates so deduced vary from around 2-9 μm min −1 and increase with increasing energy loss.…”
Section: Resultsmentioning
confidence: 99%
“…It is also demonstrated that observed LER depends crucially on the spatial resolution of methods used for etched track detection. In particular, application limits of the optical techniques for registration of ions by measuring LERs of fast ion tracks in olivine 15,17,22,29,30 are investigated.…”
Section: Introductionmentioning
confidence: 99%